Application of Indoor Mobile Robot Technology in the Construction of 3D Multimedia City Museum Exhibition Hall - Yang, Xudong; Wan, Tao (Informatica, 2024)
The advancement of science and technology has made robotics technology better developed. Robotic technology is used more and more frequently in the construction of museum exhibition halls. In the past, most museums used manual interpretation or personnel identification in the construction of exhibition halls, which had many problems. For example, the content of exhibits is unclear. The management of personnel is unscientific. The effect of face recognition is not high. In order to solve the existing problems and further reflect the role of indoor mobile robot technology in the construction of 3D multimedia city museum exhibition halls, this paper first introduced the 3D multimedia city museum. It can improve the intelligence level of the exhibition hall and bring tourists and high-end visiting experience. Next, indoor mobile robots were used in the construction of exhibition halls. By comparing it with traditional manual labor in terms of speech recognition and tourist satisfaction of 20 tourists randomly selected to score the service satisfaction of the exhibition hall, it was concluded that using robots in the exhibition hall, the satisfaction of tourists was as high as 94 points, which could better serve tourists. At the same time, it could also improve the accuracy of speech recognition. The exhibition hall using robots had a recognition rate of more than 96% for visitors to ask questions in a noisy environment.